Senkatana. - Mofokeng.,Mahase. (Wits University Press, 2021)
Senkatana is a Sesotho play based on a Basotho legend about a monster that swallowed all the people and animals except for one pregnant woman. She gave birth to a boy, Senkatana, when a young man, killed the monster. The grateful people made him their king, but soon after he was killed to settle a family score.
Keywords: Electronic books.